Amonites y bioestratigrafía del Grupo Cuyo en la Sierra de Reyes (cuenca Neuquina central, Argentina) y su significado secuencial - Spalletti, Luis Antonio (2012)
This paper deals with the stratigraphy, the systematics of the ammonite faunas and the biostratigraphy of the Cuyo Group in the Sierra de Reyes (southern Mendoza Province, Argentina). The 230 m-thick marine siliciclastic succession of the Cuyo Group is composed, from base to top, of the Bardas Blancas Formation (mudstones, sandy mudstones and fine-grained sandstones), the Los Molles Formation (black shales) and the Lajas Formation (coarse- to fine-grained sandstones). Four ammonite levels have been recognised in the Cuyo Group. The first two levels (I and II) are located in the lower section of the Bardas Blancas Formation. The monospecific level I yielded Dumortieria cf. pusilla and is regarded as upper Toarcian-lower Aalenian, whereas level II is composed of an association of Podagrosiceras cf. athleticum, Planammatoceras sp., Phylloceras sp. and Eudmetoceras? sp. which can be assigned to the upper Aalenian-lower Bajocian Malarguense Standard Zone. The third level appears in the middle part of the Bardas Blancas Formation and contains Morphoceras sp., Phylloceras sp. and Lytoceras cf. eudesianum, and is assigned to the lower Bathonian. The younger level (IV) was identified in the lower section of the Lajas Formation and yielded Iniskinites crassus, Stehnocephalites gerthi and Lilloettia cf. steinmanni. This association corresponds to the upper Bathonian Steinmanni Standard Zone. The ammonite record of the Cuyo Group in the Sierra de Reyes allowed dating the transgressive succession represented by the Bardas Blancas and Los Molles formations as late Toarcian-early athonian. The ammonite fauna identified in the lower section of the Lajas Formation (level IV) indicates that the change from transgressive to regressive conditions recorded at the upper part of the Cuyo Group occurred around early-late Bathonian times. The uppermost strata of the Cuyo Group (upper section of the Lajas Formation), having a well defined regressive signature, can be dated as lower Callovian. This relatively well constrained biostratigraphic framework of the Cuyo Group in the Sierra de Reyes and its comparison with neighbouring areas allowed for a better understanding of the sequential evolution in central Neuquén Basin during the late Lower to Middle Jurassic.